Evaluating Success in Public Health Advocacy Strategies - Moore, M.; Yeatman, H.; Pollard, Christina (Vietnam Public Health Association, 2013)
Advocacy is conducted by public health organisations with the aim to bring about policy improvement for better health outcomes. Implementation of a new policy usually requires a change in government practice, often to be managed by relatively conservative, and resistant, government agencies. To better understand the change process, relevant frameworks for managing transition can be used, such as Kotter's The 8-step Process for Leading Change, as suggested by David Butt. This paper assesses the extent to which this framework can assist health advocates to determine the best approach and to evaluate the effectiveness of what they are doing as advocates. We evaluate the Public Health Association of Australia's (PHAA) advocacy campaign to incorporate environmental and equity considerations into the Australian Dietary Guidelines and the Australian Guide to Healthy Eating using Kotter's framework. The PHAA's advocacy actions clearly aligned with Kotter's 8 Steps management change process. Two additional steps were also identified - the need to build long-term relationships and the importance of opportunistic actions. Management frameworks can assist health advocates to determine the key elements of effective advocacy, to plan structured advocacy campaigns and to evaluate their effectiveness. Although the policy case example is an Australian one, the principles of effective advocacy are applicable internationally.